The Changing Landscape of Infrastructure Finance in Africa : Nontraditional Sources Take on a Growing Role - Foster, Vivien (World Bank, Washington, DC, 2012)
Africa has traditionally depended on official development assistance to meet its infrastructure needs. But a growing share of the region's infrastructure finance is now coming from nontraditional sources. Leading this trend is non-Organization for Economic Co-operation and Development (OECD) financiers, chiefly China, India, and Arab countries. While Arab funds have been operating in Africa for decades, China and India began to step up their involvement in the early 2000s. Flows from these non-OECD sources are now broadly comparable to traditional development assistance in dollars committed. The largest flows have gone to power especially hydropower and rail transport.